Peningkatan Kepercayaan Konsumen E-Commerce di Provinsi Sumatera Utara Melalui Teknologi Informasi - Ibrahim Syahputra Harahap; Muhammad Irwan Padli Nasution (BADAN PENERBIT STIEPARI PRESS, 2024)
This study aims to determine the level of trust of the people of North Sumatra in making online purchases or often referred to as e-commerce. This research uses descriptive quantitative research using a survey approach. Distribution of questionnaires through the Google From application, with 53 respondents. Questions are carried out using a Likert scale. The results showed that 50 people believed in e-commerce by 94.3%, who did not believe in the existence of E-Commerce3 people or equivalent to 5.7%. Related to this aspect of trust that the people of North Sumatra often do e-commerce as a place to meet needs easily and practically and can be done anywhere.